'We Do Not Divide Our Champions According to Color'?: A Failed 1938 All-White Follow-Up Tour of South Africa. Issue 8 (15th July 2022) - Dyreson, Mark; Sikes, Michelle M.
ABSTRACT: In 1938 the American Amateur Athletic Union proposed a return tour of athletics stars to South Africa, recalling a 1931 trip as well as several return tours by South Africans to the US as important ventures. By the late 1930s African American athletes had become globally prominent icons of their nation, most famously Jesse Owens but also many others. US sporting bureaucrats announced the team would be selected at the 1938 national athletics championship in Buffalo. Black Americans performed exceptionally well there, including a young Jack Roosevelt Robinson (later 'Jackie') who earned a national title in the 'junior' long jump. When South Africans admitted they wanted only white athletes to tour their apartheid state, the proposed trip foundered on the rocky shoals of international sporting and racial relations. Commentators condemned not only South African apartheid but American versions of segregation as they debated the wisdom of the proposed tour in the press. The incident highlighted the global power of track and field during the era for showcasing racial justice issues as well as sparking a life-long interest in Robinson for using sport to promote racial equality not only in the US but in South Africa and around the world.